Analysis of the clinical utility of gene expression profiling in relation to conventional prognostic markers in South African patients with breast carcinoma - Grant, Kathleen Ann (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.